2014
DOI: 10.1111/jac.12103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drought on the Gas Exchange, Chlorophyll Fluorescence and Yield of Six Different‐Era Spring Wheat Cultivars

Abstract: In semi‐arid areas of north‐west China, grain yields of wheat (Triticum aestivum L.) are higher in recently bred cultivars than those released six decades earlier. The gas exchange, chloroplast activity and yield of six spring wheat cultivars grown in the 1950s, Hst and Gs96 (early), in the 1970s, Gy602 and Dx24 (intermediate), and in the 1990s, Gc20 and Lc8275 (modern) were compared with adequate water (WET) and drought stress (DRY) to determine the effects of drought stress among the cultivars. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 42 publications
2
24
0
2
Order By: Relevance
“…The reduction of ETR/P N in plants treated with EBR indicates that this steroid influences chlorophyll fluorescence and gas exchange. Guan et al (2014) evaluated early cultivars of Triticum aestivum under water deficit conditions and found increases in the NPQ values, which were related to increased thermal dissipation. The use of EBR caused a reduction in EXC due to the decrease in NPQ, which can be explained by the higher efficiency in the light capture by PSII (Silva et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of ETR/P N in plants treated with EBR indicates that this steroid influences chlorophyll fluorescence and gas exchange. Guan et al (2014) evaluated early cultivars of Triticum aestivum under water deficit conditions and found increases in the NPQ values, which were related to increased thermal dissipation. The use of EBR caused a reduction in EXC due to the decrease in NPQ, which can be explained by the higher efficiency in the light capture by PSII (Silva et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These observations, which were consistent across environments, suggest that late‐season photosynthesis was driven by the size of the reproductive carbon sink, which is largely defined by the genetic predisposition to produce higher grain numbers, successful setting those grains and the predisposition to fill them to their potential weight (Gaju et al., ; Long et al., ). Others have shown that rates of post‐anthesis photosynthesis have been upregulated as grain number has increased with wheat breeding (Gaju et al., ; Guan, Song, Wang, Turner, & Li, ; Fischer, ), and there is evidence that if sink capacity is decreased by removing filling grains, photosynthesis will decline as a feedback effect (Long et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that rates of post-anthesis photosynthesis have been upregulated as grain number has increased with wheat breeding (Gaju et al, 2016;Guan, Song, Wang, Turner, & Li, 2014;Fischer, 2008), and there is evidence that if sink capacity is decreased by removing filling grains, photosynthesis will decline as a feedback effect (Long et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Today, there is a general agreement that a decrease in photosynthesis under drought stress is because of stomatal closure that restricts the diffusion of CO 2 into the leaf or due to non-stomatal limitations, such as inhibition of Rubisco or ATP synthesis (Guan et al 2015).…”
Section: Introductionmentioning
confidence: 99%